2019
DOI: 10.1111/psyp.13403
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological indexes of option characteristic processing

Abstract: Decision making is vital to human behavior and can be divided into multiple stages including option assessment, behavioral output, and feedback evaluation. Studying how people evaluate option characteristics in the option assessment stage would provide important knowledge on human decision making. Using the event‐related potential (ERP) method, the present study investigated the neural mechanism of evaluating two types of option characteristics (i.e., reward magnitude and degree of uncertainty) in the temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The employment of EEG signals in decision-making processes under uncertainty has largely concentrated on eventrelated potential (ERP) and spectral features at the sensor level [50][51][52][53]. In our study, the sensor level results reveal greater neural responses in multiple brain regions during the second half trials compared to the first half, and similarly, during not-asked trials as opposed to asked trials (Figure 5).…”
Section: Representing Uncertainties At the Sensor Levelmentioning
confidence: 62%
“…The employment of EEG signals in decision-making processes under uncertainty has largely concentrated on eventrelated potential (ERP) and spectral features at the sensor level [50][51][52][53]. In our study, the sensor level results reveal greater neural responses in multiple brain regions during the second half trials compared to the first half, and similarly, during not-asked trials as opposed to asked trials (Figure 5).…”
Section: Representing Uncertainties At the Sensor Levelmentioning
confidence: 62%
“…However, the draw outcome of each trial would not be revealed until the participants had completed all the required tasks for the experiment to avoid the potential influence of the prior outcome on subsequent decision-making ( Zhang et al. , 2013 ; Lin et al. , 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…All the ROIs were selected based on whole-brain activation elicited by the framing effect (Table 1). For the positive effect of frame, the left amygdala (-24, -4, -10) was selected; for the negative effect of frame, the right dACC (14,20,32), left AI cortex (-40, 10, 2), and right AI cortex (36,18,10) were selected. All ROIs were extracted as 5 mm-radius spheres.…”
Section: Imaging Data Analysismentioning
confidence: 99%